THE RISK IN TOURISM - TERRORISM A THREAT FOR EUROPEAN TOURISM - Sofronov, Bogdan (Annals of Spiru Haret University. Economic Series, 2017)
The paper presents information about risk in tourism and about terrorism as a threat for European tourism. If a terrorist attack occurs in a country, then it might make people think twice about visiting that place, and they may decide to change location. Risk is defined as uncertain event management in order to success. Risk is characteristic of all methods and means by which risk is managed to achieve the objectives described in the technical event, social, human and political analyzed, having as basis the uncertainty major risk factors. Tourism is travel for pleasure or business; also the theory and practice of touring, the business of attracting, accommodating, and entertaining tourists, and the business of operating tours. Tourism may be international, or within the traveller’s country.